Enhancing high-order thinking abilities through disc socio-scientific issues discussion on the virus concept - Apriliani, Adelia Siti Nur; Herlanti, Yanti (JPBIO (Jurnal Pendidikan Biologi), 2025)
Based on national and international assessments, Indonesian students' higher-order thinking is inadequate, highlighting the need for effective learning. This study aimed to explore the impact of discussion of a socio-scientific issue on the development of higher-order thinking related to the concept of viruses. A quasi-experimental design used a nonequivalent pretest and posttest control group framework. The experimental group engaged in a socioscientific issue discussion model comprising the stages of Polemic, Exploration, Action, and Conclusion (PEAK). In contrast, the control group was instructed with a constructivist learning approach with discussion, students' presentations, and teacher explanations. The experimental group included 26 males and 46 females, while the control group had 30 males and 41 females. The findings showed that the experimental group's average pretest score was 55.1, while the control group's was 60,1. After the intervention, the experimental group achieved a posttest average of 73,3, compared to 69 for the control group. The N-gain test results demonstrated higher average gain in the experimental group (x-gain 0,5) than the control group (x-gain 0,2). Additionally, the Mann-Whitney U test indicated a significant effect of the socioscientific issue discussion learning model on students' HOTS. This model offers a promising alternative to enhance students' high-level thinking.